2020
DOI: 10.36924/sbe.2020.3101
|View full text |Cite
|
Sign up to set email alerts
|

Proactive Personality, Human Resource Management Practices, and Job Performance: A Case of Banking Sector Employees in Malaysia

Abstract: The study aims to examine the influence of human resource management (HRM) practices and proactive personality on job performance. HRM practices comprised of compensation and benefits, training and development, and performance appraisal and achievement. Employees who participated in the study are employees of commercial banks located in Klang Valley. The results reported that compensation and benefits and proactive personality have a significant and positive influence on job performance. Discussions delineated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…The findings of the study supported three hypotheses i.e., proactive personality is positively related to task performance, OCBI, and OCBO. This study supports Johari and Subramaniam (2020), who suggested that proactive employees can boost their job performance in the Malaysian banking industry. This is also supported by Viet and Tuan (2018) that proactive personality predicts job performance in Vietnamese banking.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The findings of the study supported three hypotheses i.e., proactive personality is positively related to task performance, OCBI, and OCBO. This study supports Johari and Subramaniam (2020), who suggested that proactive employees can boost their job performance in the Malaysian banking industry. This is also supported by Viet and Tuan (2018) that proactive personality predicts job performance in Vietnamese banking.…”
Section: Discussionsupporting
confidence: 87%
“…Islam et al (2018) likewise recommended that selfstarting proactive behavior is essential at the present workplace for better performance. Similarly, Johari and Subramaniam (2020) stated that proactive employees are essential for better job performance in the fast-paced working environment of the banking industry as proactive personality leads to better task performance and contextual performance (Johari & Subramaniam, 2020). Bakker et al (2012) claimed in their study that employees who were characterized by proactive personality traits were predictive of work engagement and in-role performance.…”
Section: Introductionmentioning
confidence: 99%
“…Which means that Pizza Hut Delivery as one of the subsidiaries of Pizza Hut has provided good training in the development of employees who work at the fast food restaurant. However, training and development with employee involvement as mediation has a positive but not significant impact on employee performance according to journals from (Johari &;Subramaniam, 2020), (Saluy &;Kemalasari, 2017). Therefore, it is necessary from the company to find a strategy and consistently provide training and development, provide training and development that can help improve employee performance.…”
Section: Resultsmentioning
confidence: 99%
“…Its effectiveness can improve work and help individuals maintain employee engagement (vigor, absorption, and dedication) (Liu et al, 2021). Job crafting done by employees can positively impact both employee performance and company performance (Johari & Subramaniam, 2020). Work crafting refers to an employee's capacity or skill to redesign a work independently, with or without management's input, to make it more pleasant and straightforward to perform.…”
Section: Literature Reviewmentioning
confidence: 99%